2016
DOI: 10.1016/j.ajpath.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation as a Means for Improving Vision

Abstract: Evolving research has provided evidence that noninvasive electrical stimulation (ES) of the eye may be a promising therapy for either preserving or restoring vision in several retinal and optic nerve diseases. In this review, we focus on minimally invasive strategies for the delivery of ES and accordingly summarize the current literature on transcorneal, transorbital, and transpalpebral ES in both animal experiments and clinical studies. Various mechanisms are believed to underlie the effects of ES, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
24

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 61 publications
1
79
0
24
Order By: Relevance
“…That study provided evidence that low electrical current could have positive therapeutic effects on degenerative retinal diseases, and since then, animal and human studies have reported promising results. The use of electricity in medicine is not unperceivable [6], as it is widely used in cardiology, neurology, and psychiatry, gradually emerging in orthopedics and regenerative medicine as better and faster healing of wounds and bones [7][8][9][10][11][12]. Bioelectrical signaling has been studied closely and influences the epigenetics and transcriptional cascades that control cellular migration, proliferation, differentiation, and cell death [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That study provided evidence that low electrical current could have positive therapeutic effects on degenerative retinal diseases, and since then, animal and human studies have reported promising results. The use of electricity in medicine is not unperceivable [6], as it is widely used in cardiology, neurology, and psychiatry, gradually emerging in orthopedics and regenerative medicine as better and faster healing of wounds and bones [7][8][9][10][11][12]. Bioelectrical signaling has been studied closely and influences the epigenetics and transcriptional cascades that control cellular migration, proliferation, differentiation, and cell death [13].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that low current electrical stimulation improves vision and retinal function in several eye diseases [6], such as traumatic optic neuropathy (TON) [15], central or branch retinal arterial occlusion (CRAO or BRAO) [16], dry age-related macular degeneration (AMD) [12], and retinitis pigmentosa [17][18][19]. Emerging evidence suggests that low-current electricity increases the MC's release of neurotropic factors, e.g., brain-derived neurotropic factor (BDNF) [20], ciliary neurotropic factor (Cntf) [21], fibroblast growth factor 2 (FGF-2) [22], and insulin-like growth factor-1 (IGF-1) [23].…”
Section: Introductionmentioning
confidence: 99%
“…Week factors [14,15]. Brain-derived neurotrophic factor (BDNF) is a neurotrophin that is thought to have a critical neuroprotective role in retinal disease as well as other central nervous system conditions such as Parkinson's disease [16] and deserves further attention.…”
Section: Discussionmentioning
confidence: 99%
“…Dies gab den Impuls für weitere Studien im Bereich der Elektrostimulation auch für andere retinale Erkrankungen wie der AMD. Verschiedene Applikationswege der Elektrostimulation sind in der Literatur grundsätzlich beschrieben worden wie transpalpebrale, transorbitale, transkorneale, subretinale, epiretinale, transchoroidale und die direkte Stimulation von Sehnerv oder Sehrinde [29]. Gegenwärtig ist der transpalpebrale Ansatz der am meisten verfolgte bei den laufenden und zuletzt durchgeführten AMD-Studien [30 -32].…”
Section: Elektrostimulationunclassified
“…Verschiedene Erklärungsansätze sind formuliert worden wie bspw. eine verbesserte Zellpermeabilität, eine Verbesserung der Nervenleitgeschwindigkeit, eine Erhöhung der Perfusion oder eine Reduktion von Entzündung [29].…”
Section: Elektrostimulationunclassified